Automatic left atrial segmentation from cardiac CT using computer graphics imaging and deep learning. (3rd October 2022) - Feng, R; Deb, B; Ganesan, P; Rogers, A J; Ruiperez-Campillo, S; Clopton, P; Tjong, F V; Chang, H J; Rodrigo, M; Zaharia, M; Narayan, S M
Abstract: Introduction: Segmenting left atrial (LA) substructures, including the LA body, appendage (LAA), and pulmonary veins (PVs), from computed tomography (CT) is central to electroanatomic mapping for ablation and functional studies in patients with atrial fibrillation (AF). However, this process requires manual outlining which needs special training, is subjective, and is difficult to scale. Computer graphics imaging (CGI) has been applied in media, film, and computer-aided design to reliably segment complex structures using their basic geometric representations. Purpose: We hypothesized that LA substructures can be "virtually" dissected using CGI to separate geometric contours of the "convex ellipsoid" LA, "tubular" PVs, and "conical" LAA. We further hypothesized that the results of virtual dissection can be used to train a deep learning (DL) model to segment raw CT scans. Methods: First, a mathematical method based on CGI techniques – erosion and dilation – was developed to "virtually dissect" the convex LA body from the original concave shell in publicly available digital atria with diverse simulated morphologies (Fig. 1A). The PVs and LAA were then automatically revealed and labeled by a 3D subtraction approach. Second, we refined precise LA/PV/LAA boundaries by tuning hyper-parameters from N=5 patient shells (Fig. 1B). Third, we used virtual dissection to train a DL model to segment CTs in N=20 patient atria (Fig. 1C). Finally, we applied this pipeline to segment raw CTs in a validation cohort of N=105 patients (23.8% women, 63.8±10.3Y; Fig. 1D). Results: Virtual dissection accurately identified LA/PV/LAA boundaries in the training set (Dice coefficients 89–98%). In the independent test cohort (N=105), this automated pipeline accurately segmented raw CTs with Dice 81–95% (Fig. 1D) compared to a panel of experts (p<0.001). Conclusion: CGI of basic cardiac geometry combined with deep learning in small datasets can accurately segment raw CT scans in large populations. This computational pipeline may automate and simplify cardiac image processing and ablation procedures, and could be applied to the ventricle or other organ systems for diverse therapeutic strategies or to train machine learning. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): National Institutes of Health